Quality of the Nipa Frond Particleboard Bonded with Citric acid and Sucrose - Mahdi Santoso; Ragil Widyorini; Tibertus Agus Prayitno; Joko Sulistyo (Jurnal Ilmu Kehutanan)
Utilization of natural binder for non-wood composite is still limited. Sucrose and citric acid are potential natural binding agents for composite products. Nipa (Nypa fruticans Wurmb.) was non-wood materials which are potentially to be used as an alternative raw material for particleboards. This study aimed to determine the quality of the nipa frond particleboard bonded with sucrose/citric acid (100/0, 87.5/12.5 and 75/25). Particleboards were manufactured in 25 cm × 25 cm × 1 cm dimension, the target of density 0.8 g/cm3. The variables included resin content of 20%, press time of 10 m, pressing temperature of 180°C and specific pressure of 3.6 MPa. The physics and mechanics properties of particleboard were tested in accordance to standard JIS A 5908:2003 and surface roughness was measured by following the method performed by Hiziroglu (1996). The results showed that the addition of citric acid to sucrose give a positive effect on most of the properties of the nipa frond particleboards. The particleboard bonded with sucrose/citric acid 87.5/12.5 was able to provide the best results to meet the standards of JIS A 5908: 2003. Characteristics of the particleboard was a density of 0.89 g/cm, moisture content of 10.21%, thickness swelling of 2.45%, water absorption of 23.55%, surface roughness of 5.13 ìm, internal bonding of 0.39 MPa, modulus of rupture of 9.80 MPa and modulus of elasticity of 3.19 GPa.